Estudio de factibilidad para la creación de la sucursal de distribución de cárnicos: La Gran feria de carnes "Don Sebista", en la Ciudad de La mana a partir del año 2013 - Calderón Bravo, Tania Johanna (2013)
The type of research adapted to the present work was field, allowing contact with actors of the problem; also used in bibliographic sources such as support to the project. Among the methods used, was the deductive - inductive which allowed framing the present problems, obtaining the objectives and justification of it. Market research found a 617,777 tilapia demand and offer of 80,640 tilapias, these data allowed to establish the unsatisfied demand for tilapia 420,137 2013. The size of the project, macro and micro location stood in the technical study. Included also is the organizational chart of the project, as well as the contribution of partners division, 60% (120,886.94) and the other 40% corresponds to a bank loan of 80,591.29 dollars. Followed by the financial perspectives and evaluation thereof, where are the first year income by $145,716.02. In the income statement at the end of the first year retained earnings were positive in the order of $ 28,262.80 and for the second year positively increases to. In year 1 cash flow is $ 37,376.20. Benefits and justifications for the project which include investment criteria, returns from bank loans and financial expenses, depreciation expenses, taxes and dividends. The result is an internal rate of return (IRR) of 17.97%, a net present value (NPV) of $271,677.63 and a benefit cost ratio (RB/C) of 1.56.